Challenges of and Opportunities from the Commodity Price Slump - Lucas Atkins; Deborah Brautigam; Yunnan Chen; Jyhjong Hwang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
The first edition of the China-Africa Economic Bulletin provides a comprehensive overview of the key channels of China-Africa economic engagement over the last decade, with a focus on shifting economic trends in the past five years. The collapse of global commodity prices beginning in 2014, tied with the domestic slowdown in China, has significant implications for the tenor and nature of China's economic relationship with African countries going forward. This bulletin provides more information on trends in bilateral trade, Chinese outward direct investment to Africa, Chinese labor and contract values, and Chinese loans to African governments.
Keywords: 330